Olfactory bulb differently synchronizes ventral hippocampus–medial prefrontal cortex circuit during spatial working memory across social dominance hierarchies - Elham Bakhshi Jifroudi; Soomaayeh Heysieattalab; Farhad Farkhondeh Tale Navi; Ali Jaafari suha; Faezeh Zarfsaz; Yousef Panahi (PLoS ONE, 2026)
The olfactory system plays a central role in social communications in most mammals, especially social dominance hierarchies (SDH). The olfactory bulb (OB) is intricately linked to cortical and limbic areas concerned with social and learning and memory functions. To elucidate the neural underpinnings of cognitive performance in dominance hierarchies, this study investigated how OB delta oscillations (< 4 Hz) synchronize gamma oscillatory activity (30–50 Hz) within the ventral hippocampus-medial prefrontal cortex (vHPC-mPFC) circuit in rats of varying social ranks. Twenty-one male Wistar rats were home-caged in natal triads and categorized as dominant, middle-ranked, or subordinate based on tube test performance. After a month of social cohabitation, rats underwent a spatial working memory (SWM) task in T-maze with two delay intervals: an easy level of task (30-second delay) and a difficult level of task (5-minute delay). The percentage of correct responses showed no significant difference between social ranks. However, subordinates showed lower latency in reaching the goal arm, while middle-ranked rats exhibited longer latency in the 30-second delay. Electrophysiological results revealed higher delta power spectral densities (PSDs) in OB during correct responses of the easy level of task in dominant and subordinate groups. Also, subordinates showed overall higher gamma coherence in the mPFC-vHPC circuit in positive correlation with delta PSD of OB that can be related to decreased latency during correct responses in the easy level of task. These findings highlight the engagement of the olfactory system in cognitive processes regarding social rank.